Associations of Insomnia With Hypertension and Coronary Artery Disease Among Patients With Type 2 Diabetes Mellitus - Hu, Yonghui; Yan, Zhiyue; Fu, Zhenrui; Pan, Congqing (Frontiers in Cardiovascular Medicine, 2021)
Purpose: The present study aimed to determine whether insomnia is associated with hypertension (HBP) and coronary artery disease (CAD) in a hospital-based sample of type 2 diabetes mellitus (T2DM) patients. Methods: Our present research included 354 T2DM patients. According to the diagnostic criteria of insomnia, the participants were assigned to three groups based on the duration of T2DM and insomnia diagnosis. T2DM-alone patients were placed in group A; patients with T2DM longer than insomnia were placed in group B; and patients with insomnia longer than T2DM were placed in group C. Medical history was collected from all the patients in detail. Besides, the participants underwent thorough physical examinations and laboratory measurements. Propensity score matching (PSM) was applied to evaluate the associations of insomnia with HBP and CAD. Univariate and multivariate logistic regression analysis was used to explore whether insomnia was a risk factor for HBP and CAD in T2DM patients. Results: Of 354 patients, 225 were included in Group A; 62 were included in Group B, and 67 were included in Group C. Compared with Groups B and C, Group A showed a lower prevalence of HBP and CAD (P < 0.05). In addition, compared with Group B, Group C showed no difference in the prevalence of HBP and CAD (P > 0.05). After PSM was performed, Groups B and C had a higher prevalence of HBP and CAD (P < 0.05) than Group A, with no significant difference between Groups B and C (P > 0.05). In univariate and multivariate logistic regression analysis, insomnia was a risk factor for HBP (univariate: OR=3.376, 95%CI 2.290-6.093, P<0.001; multivariate: OR=2.832, 95%CI 1.373-5.841, P=0.005) and CAD (univariate: OR=5.019, 95%CI 3.148-8.001, P<0.001; multivariate: OR=5.289, 95%CI 2.579-10.850, P<0.001). Conclusion: T2DM combined with insomnia was related to HBP and CAD, and insomnia was a risk factor for HBP and CAD in patients with T2DM. However, larger, prospective studies are required to confirm our findings.